2016
DOI: 10.1016/j.eurpolymj.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Control of molecular weight and polydispersity in polyethylene/needle-like shaped clay nanocomposites obtained by in situ polymerization with metallocene catalysts

Abstract: a b s t r a c tIn an effort to understand the influence of the shape and area of the nanoclay type used in the in situ polymerization process, two different types of clays (fibrillar and laminar) were employed to obtain nanocomposites. The preliminary results demonstrated that a needlelike shaped clay promotes higher molar mass and better mechanical properties compared with laminar clay. The ultra-high molecular weight of sepiolite/nanocomposites introduces significant problems with processability. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
0
15
0
1
Order By: Relevance
“…The in-situ polymerization method delivered well-dispersed clay fillers in a polymer matrix, which imparted an outstanding antibacterial property to the biodegradable composite material as well as an enhanced storage modulus. Herrero et al [105] investigated the influence of the shape and area of the nanoclays used in the in-situ polymerization method. Their study demonstrated that needlelike clay promotes higher molar mass and better mechanical properties compared to laminar clay; they improved the in-situ polymerization process by using a non-isothermal temperature profile and an additional amount of co-catalyst.…”
Section: In-situ Polymerization Methodsmentioning
confidence: 99%
“…The in-situ polymerization method delivered well-dispersed clay fillers in a polymer matrix, which imparted an outstanding antibacterial property to the biodegradable composite material as well as an enhanced storage modulus. Herrero et al [105] investigated the influence of the shape and area of the nanoclays used in the in-situ polymerization method. Their study demonstrated that needlelike clay promotes higher molar mass and better mechanical properties compared to laminar clay; they improved the in-situ polymerization process by using a non-isothermal temperature profile and an additional amount of co-catalyst.…”
Section: In-situ Polymerization Methodsmentioning
confidence: 99%
“…The main uses of the polyolefins are limited to commodity applications such as manufacturing pipes, industrial parts, packaging, etc and their demand in applications for high performance is very low due to their properties are not enough in these areas. To widen the usefulness of polyolefins, nanocomposites are synthesized to improve the properties of the neat polymers [1].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relative environmental impact and low cost, the nanoclays are used to form nanocomposites consisting of an organic polymer matrix dispersed with inorganic filler. Nanoclays are nanoparticles of layered mineral silicates with layered structural units that can form complex clay crystallites by stacking these layers [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, different inorganic nanoparticles have been used to improve the stiffness of polyamide matrix: nanoclays [22,23], carbon nanotubes [24,25], layered double hydroxides [26], and graphene and graphene oxide [27][28][29][30]. From all possibilities, needle-like shape nanoclays, as sepiolite, have attracted interest due to their low cost, abundance and great performance [31][32][33].…”
Section: Introductionmentioning
confidence: 99%